Fluidity improvement of semiaromatic polyamides: Modification with oligomers. Issue 7 (24th October 2013) - Zhang, Chuanhui; Huang, Xianbo; Zeng, Xiangbin; Cao, Min; Cai, Tongmin; Jiang, Sujun; Yi, Qingfeng
ABSTRACT Poly(decamethylene terephthalamide) PA10T with different relative viscosities (RV) were successfully produced by the reaction of 1, 10‐decanediamine and terephthalic acid through molecular weight regulator benzoic acid (BA). RV was shown to be decreased linearly with increasing BA concentrations and detailed structures of PA10Ts were characterized by 13C‐NMR. Fluidity of PA10T with varying molecular weight was tested and low RV PA10Ts were used as modifiers to improve fluidity behaviors of high RV PA10Ts, meanwhile mechanical properties were maintained. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40058.